Prince Saionji Japan - Clements, Jonathan 1971- (Haus histories, 2008)
The Japanese delegation at the Paris Peace Conference did not have the Japanese prime or foreign ministers with them as they had only just been elected and had plenty to do back home. The delegation was instead led by Prince Saionji Kinmochi (1849-1940), the dashing 'kingmaker' of early 20th-century Japanese politics whose life spanned the arrival of Commodore Perry and his 'black ships', the Japanese civil war, the Meiji Restoration, the Sino-Japanese War, the Russo-Japanese War, the First World War, the Paris Peace Conference and the Treaty of Versailles, and the rise of Japanese militarism. Unlike many of the conservatives of his day, Saionji was a man with experience of international diplomacy and admiration for European culture.Brought up in the days of the last Shogun, he became an active supporter of Japan's new ruling regime, after the Shogun was overthrown in a civil war, and a leading figure in the post-Restoration reform movement. In 1869, he founded the institution that would become the Ritsumeikan University - literally, 'the place to establish one's destiny'.